Nonsymbiotic Nitrogen Fixing Microbes and Urease Enzyme Activity in Peatlands Covered by Different Plant Species (Journal of Wetlands Environmental Management, 2023)
Peat soil is a soil that is rich in organic matter, hence contains many essential nutrients, such as nitrogen, to support plant growth. During the vegetative period, plants need a lot of nitrogen as a source of nutrients for plant growth. Other than soil organic matter, nitrogen can also be obtained from     N2 gas in the atmosphere by the Nitrogen Fixing Bacteria. This study aimed to determine the number of non-symbiotic nitrogen-fixing microbial populations on peatlands and their relationship with the urease enzyme activity of peat soil cultivated to sengon (Albizia chinensis), petai (Parkia speciosa), pineapple and orange. Soil samples were taken from rhizoplane of sengon, petai, pine apple, and orange in Landasan Ulin, South Kalimantan. Six soil samples were taken from each plant in wet season and dry season of 2021 and 2022. The soil samples were transported to the laboratory and used for non-symbiotic nitrogen-fixing microbial and urease enzyme determination. The data obtained were then analyzed to follow the Nested Randomized Complete Design (CRD). The results showed that the number of nitrogen-fixing microbes during dry season was more than that of wet season. The highest number of nitrogen-fixing microbes during dry season was observed in orange rhyzoplane, while the highest nitrogen-fixing microbes during wet season was observed in pane apple rhyzoplane. The number of nitrogen-fixing microbes had a positive correlation with urease enzyme activity.